Theoretical Characterization Of Square Piezoelectric Micro Ultrasonic Transducer For Underwater Applications. - Yaacob, Mohd Ikhwan Hadi; Arshad, Mohd Rizal; Manaf, Asrulnizam Abd (2010)
There are numerous advantages of employing MEMS based transducer within underwater applications. This work utilized MEMS based acoustic transducer for underwater applications.